2013
DOI: 10.1371/journal.pone.0061089
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis C Virus Core Protein Down-Regulates p21Waf1/Cip1 and Inhibits Curcumin-Induced Apoptosis through MicroRNA-345 Targeting in Human Hepatoma Cells

Abstract: BackgroundHepatitis C virus (HCV) has been reported to regulate cellular microRNAs. The HCV core protein is considered to be a potential oncoprotein in HCV-related hepatocellular carcinoma, but HCV core-modulated cellular microRNAs are unknown. The HCV core protein regulates p21Waf1/Cip1 expression. However, the mechanism of HCV core-associated p21Waf1/Cip1 regulation remains to be further clarified. Therefore, we attempted to determine whether HCV core-modulated cellular microRNAs play an important role in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…HCC patients with multiple tumor nodes, venous infiltration and advanced TNM stage showed significantly higher levels of miR-345, which was consistent with poor prognosis prediction as reported by Jiang et al (14). Although great efforts have been put into the study of miR-345 on tumor cell growth, apoptosis and metastasis (7,8,(10)(11)(12)(13), the roles of miR-345 in the modulation of EMT process remain largely unelucidated in HCC. In our recent study, gain-and loss-of-function methods were used to determine the functional roles of miR-345 in EMT.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…HCC patients with multiple tumor nodes, venous infiltration and advanced TNM stage showed significantly higher levels of miR-345, which was consistent with poor prognosis prediction as reported by Jiang et al (14). Although great efforts have been put into the study of miR-345 on tumor cell growth, apoptosis and metastasis (7,8,(10)(11)(12)(13), the roles of miR-345 in the modulation of EMT process remain largely unelucidated in HCC. In our recent study, gain-and loss-of-function methods were used to determine the functional roles of miR-345 in EMT.…”
Section: Discussionsupporting
confidence: 76%
“…We suggest that the case number and etiology may be the causes of difference. HCV core protein upregulated the expression of miR-345 in HCC cells (13), while HBV infection is the main problem in China (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An HCV core-induced Summary of the different studies that have analyzed the effect of HCV proteins on the host cell cycle. See text and references for details increase in the level of miR-345 was found to suppress endogenous p21 expression by targeting the 3′ untranslated region (UTR) of the p21 mRNA [ 117 ]. Decreases in the levels of p21 would lead to accelerated cell cycle progression, and increased p21 expression is frequently observed in human cancers [ 128 ].…”
Section: Hepatitis C Virus Modulates the G1/s Checkpointmentioning
confidence: 99%
“…Although the effect did not appear specific to HCV infected carcinomas, Wong et al (2008) noted that downregulation of miR-223 in HCC tissue appeared to promote oncogenesis by disinhibiting the Stathmin 1/oncoprotein 18 (STMN-1) oncogene. An in vitro study in Huh 7 and HEK 293 human hepatoma cell lines demonstrated a likely HCV core protein induced upregulation of miR-345, which appeared to downregulate the p21 waf1/cip to promote carcinogenesis (Shiu et al, 2013). In another in vitro study of Huh 7.5 replicons, miR-491 was noted to both increase full genome HCV clones to replicate and to downregulate cell growth inhibition on the PI3K/Akt pathway (Ishida et al, 2011).…”
Section: Methodsmentioning
confidence: 99%